JUNIOR HIGH SCHOOL STUDENTS’ CRITICAL THINKING SKILLS BASED ON SELF-RELIANCE LEARNING - Gunawan Gunawan; Irfan Saeful Hidayat; Lukmanul Akhsani; Indira Pipit Miranti (FKIP Universitas Muhammadiyah Tangerang, 2021)
The study aims to describe the students ' critical thinking skills reviewed by self-reliance learning. The research methods used are qualitative descriptive. The research subject is a grade VIII A student of SMP Negeri 3 Kalibagor which amounted to 28 people. Sampling is performed using the purposive sampling technique. In one class, selected two students with the category of the self-reliance learned to be seen, three students with the category of the self-reliance began to develop, and two students with a category of self-reliance learning culture. Collection of data using polls, tests, interviews, and documentation. The data analysis techniques used include data reduction, data presentation, and drawing concluding. The validation test used is triangulation. The results showed that more than 80% of the students who had already filled in learning independence poll included categories began to develop. Students of self-reliance category learning culture have a better critical thinking ability compared to the students ' categories begin to look and start developing. However, students with these three learning self-reliance categories do not master the evaluation capability indicator.